2014
DOI: 10.1038/ni.2885
|View full text |Cite
|
Sign up to set email alerts
|

USP15 stabilizes MDM2 to mediate cancer-cell survival and inhibit antitumor T cell responses

Abstract: Deubiquitinases (DUBs) represent a new class of drug targets, although the physiological function of only few DUBs has been characterized. Here we identified the DUB USP15 as a crucial negative regulator of T cell activation. USP15 stabilized an E3 ubiquitin ligase, MDM2, which in turn negatively regulated T cell activation by targeting the degradation of the transcription factor NFATc2. USP15 deficiency promoted T cell activation in vitro and enhanced T cell responses to bacterial infection and tumor challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
210
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(225 citation statements)
references
References 46 publications
(67 reference statements)
10
210
5
Order By: Relevance
“…To date, the first well‐studied USP in melanoma was USP13, of which the significant up‐regulation contributed to melanoma growth via deubiquitination and stabilization of melanocyte lineage‐specific transcriptional factor MITF 13. Apart from this, USP8 and USP15 have been reported to act as oncogenic factor in melanoma, highlighting that both ubiquitin‐conjugating and ubiquitin‐deconjugating enzymes played important roles in melanoma tumour biology 31, 32. In the present study, we found that USP4 was another novel oncogene belonging to USP family with integrated effects on inhibiting cell apoptosis and facilitating tumour metastasis, further revealing the close linkage between dysregulated ubiquitination and cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the first well‐studied USP in melanoma was USP13, of which the significant up‐regulation contributed to melanoma growth via deubiquitination and stabilization of melanocyte lineage‐specific transcriptional factor MITF 13. Apart from this, USP8 and USP15 have been reported to act as oncogenic factor in melanoma, highlighting that both ubiquitin‐conjugating and ubiquitin‐deconjugating enzymes played important roles in melanoma tumour biology 31, 32. In the present study, we found that USP4 was another novel oncogene belonging to USP family with integrated effects on inhibiting cell apoptosis and facilitating tumour metastasis, further revealing the close linkage between dysregulated ubiquitination and cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MDM2 and PPM1D were among the top 15 candidates. USP15, another validated top candidate, has also been shown to affect p53 levels via MDM2 stabilization (Zou et al 2014). In the E6 sublibrary screen, we identified RHOA, a Rho GTPase protein at the top of the scored gene list that is involved in negatively regulating multiple INK4 family genes, including p16…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that some of the validated genes are involved in the p53 or cell cycle regulation. For example, USP15 was shown to stabilize MDM2 to promote p53 degradation (Zou et al 2014), which could explain why it scored. We noticed that the TP53I13 and the DLX6 ORFs appeared to be truncated in the ORFeome library when compared with the NCBI reference sequence; therefore, further analysis of full-length ORFs will be required to elucidate the function of these ORFs in senescence.…”
Section: Validation Of Selected Screen Candidatesmentioning
confidence: 99%
“…Very recently, USP15 was shown to target MDM2 with effects on the stability of both p53 and the T-cell transcription factor, NFATc. Thus, USP15 inhibition could result in direct tumor cell apoptosis and increased T-cell responsiveness (19).…”
Section: Usp-associated Mutations and Gene Fusions In Hematologic Malmentioning
confidence: 99%